Enhanced drought and heat stress tolerance of tobacco plants with ectopically enhanced cytokinin oxidase/dehydrogenase gene expression - Macková, Hana; Hronková, Marie; Dobrá, Jana; Turečková, Veronika; Novák, Ondřej; Lubovská, Zuzana; Motyka, Václav; Haisel, Daniel; Hájek, Tomáš; Prášil, Ilja Tom; Gaudinová, Alena; Štorchová, Helena; et al. (Journal of experimental botany, 2013)
Responses to drought, heat, and combined stress were compared in tobacco (Nicotiana tabacum L.) plants ectopically expressing the cytokinin oxidase/dehydrogenase CKX1 gene of Arabidopsis thaliana L. under the control of either the predominantly root-expressed WRKY6 promoter or the constitutive 35S promoter, and in the wild type. WRKY6:CKX1 plants exhibited high CKX activity in the roots under control conditions. Under stress, the activity of the WRKY6 promoter was down-regulated and the concomitantly reduced cytokinin degradation coincided with raised bioactive cytokinin levels during the early phase of the stress response, which might contribute to enhanced stress tolerance of this genotype. Constitutive expression of CKX1 resulted in an enlarged root system, a stunted, dwarf shoot phenotype, and a low basal level of expression of the dehydration marker gene ERD10B. The high drought tolerance of this genotype was associated with a relatively moderate drop in leaf water potential and a significant decrease in leaf osmotic potential. Basal expression of the proline biosynthetic gene P5CSA was raised. Both wild-type and WRKY6:CKX1 plants responded to heat stress by transient elevation of stomatal conductance, which correlated with an enhanced abscisic acid catabolism. 35S:CKX1 transgenic plants exhibited a small and delayed stomatal response. Nevertheless, they maintained a lower leaf temperature than the other genotypes. Heat shock applied to drought-stressed plants exaggerated the negative stress effects, probably due to the additional water loss caused by a transient stimulation of transpiration. The results indicate that modulation of cytokinin levels may positively affect plant responses to abiotic stress through a variety of physiological mechanisms.
Keywords: proteiny huseníčku; exprese genu; Gene Expression; heat stress; Oxidoreductases; Arabidopsis; cytokinin oxidase/dehydrogenase; Droughts; Arabidopsis Proteins; promotorové oblasti (genetika); oxidoreduktasy; Cytokinins; regulace genové exprese u rostlin; cytokininy; drought stress; Plants, Genetically Modified; Abscisic acid; Nicotiana; cytokinin; Gene Expression Regulation, Plant; Promoter Regions, Genetic; vysoká teplota; geneticky modifikované rostliny; tobacco; tabák; Hot Temperature; období sucha